Entrepreneurship education in some European countries and suggestions for Vietnam - Le Thi Kim Oanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
In the context of globalization and rapid technological advancement, entrepreneurship education is becoming a crucial factor in preparing the younger generation to adapt and innovate. Many countries around the world have recognized the importance of equipping youth with the knowledge and skills necessary for entrepreneurship. Germany and Finland are two notable examples where entrepreneurship education is not only integrated into the curriculum but also supported by strong policies from the government and businesses. In Germany, the entrepreneurship education system combines theory with practice, encouraging students to engage in real-world projects. Meanwhile, Finland stands out with its innovative education model, which helps students develop an entrepreneurial mindset from an early age. Drawing from these valuable experiences, Vietnam can also identify suitable pathways to promote entrepreneurship education, contributing to economic development and creating more job opportunities for the younger generation. Code: 24101502